Improvement of key elements of sports technique based on the biomechanical analysis of Yurchenko vault - Potop, V. (Science, Movement & Health, 2013)
The goal of the work is the improvement of the key elements of sports technique by an efficient use of the didactic technology for Yurchenko vault. Methods and procedures. This scientific approach led to the conduct of an experimental study in the Junior team of Deva, applied to a group of 10 female gymnasts, 12 to 14 years old. We used in this research the following methods: bibliographic study method; observation method; video-biomechanical method; "KyPlot" statistical-mathematical method and "Excel" graphical representation method. The biomechanical analysis was made by means of a specialized program called Physics ToolKit Version 6.0, monitoring the key elements of sports technique (according to Boloban, V., 1990): start position of the body (PP), multiplication of position of the body (MP) and final position (FP) of the body. Results. The results of the study highlight the didactic technology of improvement of key elements of Yurchenko vault. The biomechanical characteristics of video analysis of Yurchenko vault have contributed to the creation of linear-branched algorithmic programs meant to improve the key elements of sports technique in terms of trajectories of body segments, height and length of the 2nd flight and the influence of the biomechanical indicators on the correct execution of the vault. Conclusions. The creation of linear-branched algorithmic programs for each key element of Yurchenko vault contributed to the improvement of the technical execution and to the achievement of better performances in competition.